Growth, Hematology and Serology of Broiler Chickens Fed Different Cultivars of Sorghum as Replacement for Maize in the Semi-Arid Zone of Nigeria - Kwari, I.D.; Diarra , S.S.; Diarra , S.S.; Saleh, B.; Bovoa, P.R.; Ramat, O.A.; Tochukwu, D. (International Journal of Poultry Science, 2011)
An experiment was conducted at the University of Maiduguri Poultry Research Farm to investigate the total replacement of maize grain with different cultivars of sorghum in broiler finisher diets. Two hundred and forty broiler chickens aged 28 days weighing 540.96±9.26 g were randomly allotted to 24 pens. Six finisher diets containing 20% crude protein were formulated for the experiment. Diet 1 (control) was based on maize which was replaced in the other diets by one of five cultivars of sorghum grain. Each of the diets was fed to 4 randomly selected pens of 10 birds per pen using a completely randomized design. Feed intake, weight gain and final body weight were all reduced (p